Clinical experience in intracranial stenting of Wingspan stent system under local anesthesia - Lin, Mao-Shih; Huang, Chih-Wei; Tsuei, Yuang-Seng (Frontiers in Neurology, 2024)
Objective: The use of endovascular treatments for symptomatic intracranial atherosclerosis disease (ICAD) remains contentious due to high periprocedural complications. Many centers resort to general anesthesia for airway protection and optimal periprocedural conditions; however, this approach lacks real-time monitoring of patients' neurological status during procedures. In this study, we employed intracranial stenting with the Wingspan system under local anesthesia to address this challenge.Methods: We conducted a retrospective study of 45 consecutive ICAD patients who underwent intracranial stenting with the Wingspan system at our hospital from August 2013 to May 2021. These stenting procedures were performed under local anesthesia in a hybrid operation room. Neurologic assessments were conducted during the procedure. The patients with periprocedural complications were analysis the risk factors. Results: The study included 45 ICAD patients (median age 62 years; 35 male, 10 female). Among them, 30 patients had anterior circulation ICAD, and 15 had posterior circulation ICAD. The periprocedural complication rate was 8.9% (4/45), with an overall mortality rate of 2.2% (1/45).Notably, no procedure-related perforation complications were found, and all ischemic complications occurred in the perforating bearing artery, specifically in patients with stents placed in the middle cerebral artery or basilar artery, while no complications were observed in the non-perforating bearing artery of internal carotid artery and vertebral artery (p = 0.04).Conclusions: Our study demonstrates the safety and efficacy of the Wingspan stent system when performed in selected patients under local anesthesia. This approach seems to reduce proceduralrelated morbidity and be a safe intervention. Besides, it is crucial for surgeons to be aware that patients with perforator-bearing artery stenosis may be at a higher risk of complications.